Modelling of miniaturized rectangular microstrip antenna using epoxy-barium titanate nanocomposite substrate for Wi-Fi applications - Nurulfadzilah, Hasan; Nurul Hazlina, Noordin; Mohamad Shaiful, Abdul Karim; Nurhafizah, Abu Talip Yusof; Noor Zirwatul Ahlam, Naharuddin (Springer, 2024)
Increasing demand for miniaturized antennas in wireless communication systems has driven research on antenna miniaturization. This paper focuses on the miniaturization of a rectangular microstrip patch antenna, a commonly used antenna in wireless communication. To achieve miniaturization, a high permittivity substrate, specifically an Epoxy-Barium Titanate nanocomposite, is employed as a replacement for the conventional substrate, FR4. Different compositions of epoxy filler (90:10, 80:20, 70:30, and 60:40%) are investigated to determine the optimal design. The design and simulation are performed using CST Studio Suite software at the Wi-Fi frequency of 2.4 GHz. Experimental measurements are conducted to evaluate the antennas’ performance in terms of S11, VSWR, efficiency, gain, and directivity. Among all the antennas with epoxy-barium titanate substrates, the antenna with a 20% epoxy-barium titanate composition exhibits the best performance at the Wi-Fi frequency of 2.4 GHz. Finally, the optimized antenna design with the 20 and 30% epoxy-barium titanate substrate has potential to be fabricated.